Viewpoint: PHILOSOPHY IN TEACHER EDUCATION: SOME PERSONAL REFLECTIONS - O’Dea, Jane (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1992)
No longer content to remain at the margins of practice, philosophy of education has, in recent years, taken a new turn. It has come to see itself, at least in part, as a genre of applied philosophy, one very much concerned with developing students’ awareness of the concrete ethical problems teachers and administrators face during their careers, and with increasing their ability to deal with these problems in a responsible, ethically informed manner. In concerning itself thus with practical issues, philosophy of education has entered a new and exciting phase, one that gives it a much more relevant and dynamic role in teacher education. The potential personal significance, for student teachers, of this new more practical approach is discussed. RÉSUMÉ Pas jamais content de rester à la périphérie, la philosophie de l’éducation a récemment pris une nouvelle direction. Elle se considère, de plus en plus, une catégorie de la philosophie appliquée - c’est à dire, ce que s’occupe de développer un compréhension des problèmes morals qui confrontent des enseignants et des directeurs d’écoles de nos jours. D’ailleurs, elle s’agit d’améliorer la capacité des étudiants de résoudre ces problèmes dans une manière morale et responsable. En embraçant des questions practiques, la philosophie de l’éducation d’aujourd’hui est plus pertinent à laformation des enseignants. On discute l’importance de ce nouvelle conception pour les stagiaires.